2016
DOI: 10.1038/srep19229
|View full text |Cite
|
Sign up to set email alerts
|

FAS rs2234767 and rs1800682 polymorphisms jointly contributed to risk of colorectal cancer by affecting SP1/STAT1 complex recruitment to chromatin

Abstract: FAS rs2234767 (−1377 G>A), rs1800682 (−670 A>G) and FASLG rs763110 (−844 C>T) promoter polymorphisms can influence transcriptional activities of the genes and thus multiple tumors susceptibility. To investigate their association with risk of colorectal cancer (CRC), the three SNPs were genotyped in 878 cases and 884 controls and the results showed that the FAS rs2234767 and rs1800682 were in a high linkage disequilibrium (LD) with each other (D’ = 0.994) and jointly contributed to an increased risk of CRC (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…Additionally, siRNA knockdown experiments showed that C/EBPβ played a more important role than the function of OCT1. Similarly, we demonstrated that the rs2234767 and rs1800682 polymorphisms might contribute to the risk of colorectal cancer by regulating the SP‐1/STAT1 complex to the FAS gene promoter region . Therefore, we speculate that the interactions among the different transcription factors may play a significant role in the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, siRNA knockdown experiments showed that C/EBPβ played a more important role than the function of OCT1. Similarly, we demonstrated that the rs2234767 and rs1800682 polymorphisms might contribute to the risk of colorectal cancer by regulating the SP‐1/STAT1 complex to the FAS gene promoter region . Therefore, we speculate that the interactions among the different transcription factors may play a significant role in the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 62%
“…e ). Sp1, a reported FAS regulator, as well as HDAC1 and p300, were detected on FAS promoter (Fig. f ).…”
Section: Resultsmentioning
confidence: 99%
“…The Fas rs1800682 polymorphism is located in a STAT1 binding element on the Fas promoter, which has been linked to the downregulation of Fas expression. 22 The FasL gene rs763110 polymorphism lies within a putative binding motif for the CAAT/enhancer-binding protein β-transcription factor. 41 Our results suggest that the Fas rs1800682 SNP may be associated with an increased risk of breast cancer, while the FasL rs763110 polymorphism may decrease breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies revealed that Fas/FasL gene polymorphisms are associated with susceptibility to various types of cancer, including cervical, 11 14 pharyngeal, 15 17 digestive, 18 22 and breast cancer. 23 28 Further studies demonstrated that circulating, soluble Fas (s Fas ) can inhibit Fas -mediated apoptosis by neutralizing the FasL or the anti- Fas antibodies, 29 while increased levels of s Fas have been observed in serum from patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%